Incidence and Risk Factors of Post-Thyroidectomy Stridor - Salih Abdul-Zahra, Aziz; Hameed Abd Al-Helfy, Sajid; Abass Abdulhassan, Bashar (Diyala Journal of Medicine, 2023)
Background: Thyroidectomy is a common procedure performed by the general surgeons. Stridor is an airway sign caused by a variety of post-thyroidectomy complications. Objective: To determine the incidence of post-thyroidectomy stridor and the risk factors associated with its occurrence. Patients and Methods: The study included 280 adult patients who had total or partial thyroidectomy performed by various surgeons. Patients were followed up for 6 months after they were discharged from the hospital. Data collected included demographic information, type of thyroid disease, duration of illness before surgery, type of surgery, number of intubation attempts, and the presence of hoarseness and hematoma post-operatively. Results: Only eighteen patients (6.43%) who underwent thyroidectomy developed stridor during the follow-up period. They were compared to 25 other patients who were chosen from the original sample based regular visit of patients during the follow up. Higher body mass index (BMI), bilateral thyroidectomy, presence of concomitant hoarseness and hematoma, and more than one attempt at intubation were all associated with an increased risk of post-thyroidectomy stridor. Conclusion: Stridor affects only a small percentage of patients undergoing thyroidectomy. Increased BMI, bilateral thyroidectomy, presence of concomitant hoarseness and hematoma, and frequent tracheal intubation are the most common risk factors for post-thyroidectomy stridor.